Prevalence and community awareness of Bovine Trypanosomiasis in Wolaita Zone Kindo Koysha Woreda, Southern EthiopiaEast African Journal of Biophysical and Computational SciencesEast Afr. J. Biophys. Comput. Sci.(2020), Vol. 1, Issue 1, 23 -34 - Seifemichael Ushencho; Amene Fekadu (East African Journal of Biophysical and Computational Sciences, 2020)
A cross-sectional study was carried out from October 2018 to April 2019 in Kindo Koysha Woreda of Wolaita Zone, Southern Nation Nationalities and People Region (SNNPR), Ethiopia. The general objectives were to find the prevalence and assess the community awareness on bovine trypanosomiasis and to identify predominant trypanosome species. Blood from marginal ear vein was collected from a total of 220 cattle for Packed cell volume (PCV) determination and trypanosome detection. Accordingly, the overall prevalence of bovine Trypanosomiasis in the area was 5.91% on Buffy coat examination. Of which, 61.57% (n=8), 30.76% (n=4) and 7.69% (n=1) were because of T. congolense or T. vivax or both species, respectively. The mean PCV values recorded were 23.77% in parasitemic and 28.27% in aparasitemic animals. The focus group discussion indicated that trypanosomiasis (Shulula) is the most important problem affecting the animals and hindering agricultural activity in the area. Generally, both focus group discussion and hematological findings revealed bovine trypanosomiasis is the major constraint for the livestock production in the area. So attention should be given to control trypanosomiasis and its vectors